Activity enhancement of copper doped TiO2/ZnO photo catalyst for degradation of recalcitrant pollutants / Mohammad Reza Delsouz Khaki - Mohammad Reza, Delsouz Khaki (2017)
Industrial wastewaters contain a variety of chemical pollutants such as phenolic compounds , dyes, organophosphate insecticide. Treatment of these chemical compounds is of importance due to the toxic nature of these chemical compounds. Advance Oxidation Processes (AOPs) have been introduced as a potential method to produce highly oxidative ion species including OH● and O2.− for water treatment. Photocatalysts such as TiO2 and ZnO have been extensively and successfully used in AOPs to remove chemical pollutants. However, these photocatalysts suffer from limited activities and applications under UV light due to large band gap. Doping is the process of adding transition metals to a photocatalyst or combining two different photoctalysts to alter their properties, especially their band gap energy level. In this study, a new photocatalyst, Cu-doped TiO2/ZnO nanocrystals were fabricated by entrapping copper ions in the crystalline matrix of TiO2/ZnO through sol-gel method in order to improve the photocatalytic activity of TiO2. Different copper concentrations were loaded into the photocatalyst matrix and the photocatalysts were calcinated at two different temperatures of 500 and 700°C. Thermal property, crystalline structure, surface morphology, band gap and absorption spectra of Cu- TiO2/ZnO were characterized by thermogravimetric analysis, X-ray diffraction, scanning electron microscopy, transmission electron microscope and UV–Vis spectroscopy. The minimum crystal size and maximum surface area were observed in the samples with Cu amount of 5wt%. It was also observed that the Cu-TiO2/ZnO complex was in cylindrical shape, depending on the concentration of the compounds. Furthermore, the band gap of Cu-TiO2/ZnO was reduced to about 2.20ev as the Cu loading increased to almost 3%. The photocatalytic activity and stability of the photocatalyst with the best characterization result were then evaluated based on its capability of degrading methyl orange and methylene blue dyes based on colour, COD and TOC removal under visible light irradiation. The characterization results implied that the synergistic effect of Cu ions considerably narrowed the band gap of TiO2 and ZnO compared to TiO2, ZnO, TiO2/ZnO, Cu-TiO2 and Cu-ZnO. The synthesized photocatalysts also showed enhanced absorption in the visible light region, exhibiting the ability of Cu-TiO2/ZnO for photocatalytic degradation of these model dyes. Cu- TiO2/ZnO with a Cu content of 3wt% was found to have the maximum activity, giving C/C0 value of 0.03 after 150 min. The maximum colour removal of 85.45%, COD removal of 70.56% and TOC removal of 48.70% were achieved for MO while the maximum colour removal of 73.20 %, COD removal of 59.92% and TOC removal of 38.77% were achieved for MB under optimal conditions. ANFIS (Adaptive Neuro Fuzzy Inference System) was used to analyse the sensitivity of photoactivity of Cu-TiO2/ZnO towards operating conditions in advanced oxidation reaction for photodegradation of dyes. According to variables selection using ANFIS analysis, catalyst concentration 0.6 g/l and reaction time 120 min were the most effective parameters for MO degradation whereas dye concentration 35 ppm and pH > 7.5 were the most influential on MB removal using Cu-TiO2/ZnO.